تطبيق ّ الميراث الشرعي : ّ بدلا من نطام الميراث العرفي بلاد يورʪ ة ّ النيجيري أنموذجا - Shittu Bilal Yusuf; Nik Rahim Nik Wajis; Irwan Mohd Subri; Alawiye Abdul Mumin Abdur Razzaq (Universiti Sains Islam Malaysia, 2024)
MJSL 2018-dec